A study on relational factors in information technology outsourcing: analyzing judgments of small and medium-sized supplying and contracting companies' managers. Issue 4 (13th August 2021) - de Carvalho, Victor Diogho Heuer; Poleto, Thiago; Nepomuceno, Thyago Celso Cavalcante; Costa, Ana Paula Paula Cabral Seixas
Abstract : Purpose: Understanding the relational factors in information technology outsourcing (ITO) processes is essential for managers to exercise successful governance over their relationship. Based on this premise, this paper aims to present a study about relational factors using judgments of managers from small and medium-sized supplying and contracting companies involved in ITO relationships, helping to understand the differences between what they believe to be relevant for maintaining the relationships. Design/methodology/approach: The analytical approach consisted of applying fuzzy sets theory elements, converting the managers' judgments into crisp values through a defuzzification process, and the multicriteria method ELECTRE IV that created the rankings of the relational factors according to the defuzzified judgments. The approach was applied with 16 managers from supplying companies and 34 from contracting companies, in both cases located in a large Brazilian pole of information technology. Findings: The main findings indicate that suppliers are initially more concerned with contractual aspects, being in the highest positions in the ranking: detailed contract, service level agreement and costs. Only after these elements, suppliers prioritize aspects less linked to the contract. For contractors, customer relationship management is the most important, followed by costs and commitment by managers, which indicates more openness to issues-oriented to relational development. Originality/value: The approach adopted in this article is differentiated by prioritizing relational factors that are not always directly perceived in ITO relationships. Another important consideration is that most studies focus only on the perspective of supplier selection by contracting companies. In this paper, both suppliers' and contractors' judgments on the importance of ITO relational factors were analyzed, creating rankings that supported understanding the difference between the two perspectives.